Public Management Importation Control Activities from The Perspective of Good Governance - Alfi Haris Wanto; Yusuf Efendi (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
One of the functions of customs and excise is as a community protector that aims to protect the public from importing dangerous goods into Indonesia. On the other hand, customs as a government institution is closely related to public services because one of the government's responsibilities is to provide services to stakeholders/society. Supervisory activities carried out by customs and excise as a function of the community protector are closely related to public services. Therefore, the principles of good governance must be applied in supervisory activities. This paper aims to analyze the supervision activities carried out by Customs and Excise based on the principles of good governance. The type of research used in this research is qualitative research, which uses interviews, observation, and documentation. Based on the research results, the supervision activities carried out by the Customs and Excise Intelligence Analyst have not fully implemented good governance, especially in transparency, responsiveness, consensus-oriented, equity inclusiveness, effectiveness, and efficiency.